Adaptive soft starter for a three‐phase induction‐motor driving device using a multifunctional series compensator. Issue 7 (9th May 2019) - Jiang, Fei; Tu, Chunming; Guo, Qi; Wu, Zhengyu; Li, Yinyi
Abstract : This study proposes an adaptive soft starter control for induction motors using a multifunctional series compensator (MFSC). The proposed MFSC can operate in two modes: (i) the compensation mode for voltage sags and (ii) the virtual impedance mode for soft starting. Various MFSC functions are obtained by controlling the output characteristics of the series inverter. In the voltage sag compensation mode, a voltage is injected in series with the fault phase; as a result, the terminal voltage of the motor remains constant. In the soft‐starter mode, the proposed converter injects adjustable virtual impedance in each phase; as a result, the starting current can be limited to the desired value. A novel control scheme and the optimal parameter selection of the MFSC are also presented. The design methodology of the proposed MFSC is verified using simulations conducted in MATLAB/Simulink software. Experimental results prove the capability and effectiveness of the proposed MFSC.